The effects of task organization on skill and knowledge in physical education. (Efecto de la forma de organización sobre el aprendizaje técnico y conceptual en educación física). - Antonio Calderón; Peter Andrew Hastie; Jose Manuel Palao; Enrique Ortega (Ramón Cantó Alcaraz, 2013)
Abstract The study examined the effects of different methods of practice three track and field skills (hurdles, high jump and shot put) on students performance, from both qualitative (systematic observation), and quantitative (time, height, and distance) perspectives, and also their knowledge of the events. One hundred and twenty-two students (71 boys and 51 girls of 13.4±1.2 years) from a high school participated in nine lessons in which they used three different types organization of practice. Results show that the organization of practice had a significant effect on performance for lower and medium skill level students, but improvements differed across events. For example, students made significant improvements in shot put when practicing in lines, and for hurdles when practiced in games. These results reinforce the idea that is important for physical education teachers these variables when planning lessons. Resumen El estudio examinó el efecto de tres formas de organización (filas, circuitos y juegos) sobre el aprendizaje técnico y conceptual de tres habilidades atléticas (vallas, salto de altura y lanzamiento de peso). Ciento veinte y dos estudiantes (71 chicos y 51 chicas de 13,4 ± 1,2 años) de Educación Secundaria, participaron en nueve sesiones de enseñanza-aprendizaje durante la clase de educación física, en las que se utilizaron los tres tipos de organización de la práctica. Los resultados muestran que el tipo de organización tuvo un efecto significativo sobre el aprendizaje técnico y conceptual, en alumnos con nivel de habilidad bajo y medio, aunque con diferencias entre las disciplinas. Así por ejemplo, los alumnos mejoraron significativamente en lanzamiento de peso cuando practicaron en filas, y en vallas cuando practicaron en juegos. Estos resultados refuerzan por tanto la idea que es estas variables deben ser tenidas en consideración por los profesores de educación física cuando planifican sus sesiones. http://dx.doi.org/10.5232/ricyde2013.03104